Career Expectations in Certified Internship and Independent Study Students (MSIB) - Wong, Aurora Cindy; Kindangen, Ivana Alessandra; Christian, Daniel; Budiarto, Yohanes (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The relationship between internship experiences and career expectations among students has become an increasingly interesting topic for academics and practitioners alike. This study focused on 108 active student participants, both female and male, who had internship experiences at companies across four different sectors: retail, media, hospitality, and technology. The researcher employed a quantitative method using the Career Expectations Questionnaire, consisting of 24 items translated into Indonesian. This scale encompasses eight dimensions: competition, freedom, management, life balance, learning, entrepreneurship, organization membership, and expertise. The results indicated that female students tend to have higher career expectations than male students, while 19-year-old students demonstrated the highest career expectations compared to other age groups. Additionally, internship experiences in technology companies yielded more positive career expectations than other sectors. The study also identified competition and expertise as the primary contributors to career expectations. Hubungan antara pengalaman magang dan ekspektasi karir pada mahasiswa telah menjadi topik yang semakin menarik perhatian di kalangan akademisi dan praktisi. Penelitian ini memfokuskan pada subjek penelitian berjumlah 108 partisipan yang merupakan mahasiswa aktif berjenis kelamin perempuan maupun laki-laki yang memiliki pengalaman magang di sebuah perusahaan dan berasal dari 4 jenis perusahaan yang berbeda, diantaranya perusahaan ritel, media, hospitality, dan teknologi. Peneliti menerapkan metode kuantitatif dengan menggunakan Career Expectations Questionnaire yang terdiri dari 24 item yang telah diterjemahkan dalam bahasa Indonesia. Skala ini memiliki 8 dimensi yaitu competition, freedom, management, life balance, learning, entrepreneur, organization membership dan expertise. Hasil penelitian menunjukkan bahwa mahasiswa perempuan cenderung memiliki ekspektasi karir yang lebih tinggi dibandingkan laki-laki, sementara mahasiswa berusia 19 tahun menunjukkan ekspektasi karir yang paling tinggi dibandingkan kelompok usia lainnya. Selain itu, pengalaman magang di perusahaan teknologi menghasilkan ekspektasi karir yang lebih positif dibandingkan sektor lainnya. Penelitian ini juga mengidentifikasi aspek competition dan expertise sebagai kontributor utama terhadap ekspektasi karir.